2007
DOI: 10.1177/0193841x07306745
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Effect of On-Site 12-Step Meetings on Post-Treatment Outcomes among Polysubstance-Dependent Outpatient Clients

Abstract: Rates of return to active substance use after addiction treatment tend to be high; participation in 12-step fellowships (e.g., Alcoholics Anonymous) reduces relapse rates but many clients do not attend or attend for a short period only. This quasi-experimental study uses repeated measurement to explore the role of presence/absence of onsite 12-step meetings during treatment on post-treatment outcomes. Polysubstance-dependent clients (N = 219) recruited at a program with and one without 12-step onsite, were fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…The instrument consisted of measures and inventories summarized below, all of which we have used in previous federally funded studies of persons in SUD remission (Kaskutas et al, 2014; A. Laudet, 2007; A. Laudet, Stanick, & Sands, 2007; A.…”
Section: Methodsmentioning
confidence: 99%
“…The instrument consisted of measures and inventories summarized below, all of which we have used in previous federally funded studies of persons in SUD remission (Kaskutas et al, 2014; A. Laudet, 2007; A. Laudet, Stanick, & Sands, 2007; A.…”
Section: Methodsmentioning
confidence: 99%
“…Professional substance user treatment is effective at promoting reductions in substance use and improvements in related functioning (Magura, Laudet, Kang, & Whitney, 1999;Mojtabai & Graff Zivin, 2003;Simpson, Joe, & Broome, 2002;Teesson et al, 2006); however, treatment lasts a relatively short period of time, even when clients complete the planned duration of services. Treatment gains tend to be shortlived and post-treatment rates of return to substance use are high, often occurring within a short time after services end (Gossop, Stewart, Browne, & Marsden, 2002;Laudet, Stanick, & Sands, 2007). It is therefore important to identify non-treatment factors that promote the maintenance of treatment gains into the post-treatment period; these factors may also be useful to persons who wish to stop using drugs and/or alcohol without seeking professional help -'selfchangers' (Toneatto, Sobell, Sobell, & Rubel, 1999;Sobell et al, 2001).…”
Section: What Does It Take To Recover? Factors Associated With Reductmentioning
confidence: 99%
“…In spite of these high rates of 12-step participation, we have documented high rates of attrition from both AA and NA among drug-dependent samples (Laudet, Stanick, & Sands, 2007). For example, in the outpatient sample, among clients who had attended 12-step at intake, 85% reported having attended NA and dropped out for a month or longer, and 91% reported a similar patterns for AA; mean number of interrupted attendance for a month or longer since attendance began was 6 (6.1 in NA, 5.4 in AA) (Laudet et al, 2004).…”
Section: Utilization Of and Experiences With Drug Recovery 12-step Fementioning
confidence: 77%
“…Information is needed on the differential effectiveness of AA and NA among drug dependent persons to inform clinicians' referral and service delivery. We have shown that the mere presence of a 12-sep group onsite in outpatient treatment, a cost-free strategy easily implemented through AA or NA's H&I for any treatment program that requests it, enhances nearly three-fold the likelihood of 12-step engagement during treatment as well as nearly six times the likelihood of continuous abstinence from drug one year after treatment ends (Laudet et al, 2007). In our remitted sample of polysubstance users, continuous 12-step attendance over the three year study duration was associated with odds two to five times greater of sustaining continuous drug abstinence over three years, compared to less than continuous participation (Laudet & White, 2007).…”
Section: Discussionmentioning
confidence: 99%